Theoretic study of the voice traffic capacity over cognitive radio networks - Tan, Cindy Shi Yan. (2012)
This project report presents the voice traffic capacity analysis over a Cognitive Radio environment. Investigations are performed to determine the traffic capacity for cognitive unlicensed users in a simulation system with presence of licensed users. Licensed users are people who have preemptive priority. Unlicensed Users are the opportunistic people who access the network channel without any interference. Each of the unlicensed users equipped themselves with a spectrum sensing cognitive radio ability to detect unused radio frequency spectrum.